Nanopartículas poliméricas de policaprolactona para entrega tópica do fotossensibilizante azul de metileno na terapia do câncer de pele em associação à sonoforese - Lima, Thayane Soares (2023)
Squamous cell carcinoma (SCC) is a subtype of non-melanoma skin cancer that originates in epidermal cells and represents about 20% of cases. The conventional treatment is surgical excision, but not all patients are candidates for this procedure. In this context, alternative therapies that use the topical route, such as photodynamic therapy (PDT), gain great relevance. PDT is based on the production of free radicals that induce the death of cancer cells. Methylene blue (AM) stands out as a photosensitizer, however, due to its hydrophilic nature and rapid enzymatic reduction in the biological environment, its ability to penetrate deeper layers of the skin is limited. Therefore, to increase the skin penetration of the drug, some strategies are used, such as the association of nanocarriers and physical methods. The main objective of the present study is to develop polymeric nanoparticles for topical delivery of AM, whether or not associated with the use of sonophoresis for the treatment of SCC through PDT. The nanoparticles were developed using the double solvent emulsification-evaporation technique and characterized physicochemically, resulting in an average size of 156.93 nm ± 8.26, polydispersity index of 0.11 ± 0.05, encapsulation efficiency of 94.22% ± 2.19 and zeta potential of -10.08 mV ± 1.12. Morphological evaluation by scanning electron microscopy showed spherical nanoparticles. FTIR allowed a qualitative analysis, in which the spectra of nanoparticles with and without drug were similar, thus inferring an almost complete encapsulation of the drug. The reagent 1,3-diphenylisobenzofuran (DPBF) was used to detect the production of reactive oxygen species, in which the nanoparticle showed a more sustained profile. In vitro release studies using the passive method show the nanoparticle compatible with the first- order mathematical model. The skin penetration study passively and with sonophoresis was carried out using intact pig ear skin, with quantification of the drug in different strata using UV-Vis spectrophotometry in which a higher concentration of AM was observed in the epidermis + dermis after sonophoresis, corresponding to 24.31 and 23.81 μg/cm2, for solution and nanoparticle, respectively. The MTT assay was used to evaluate cytotoxicity in cells of the human squamous cell carcinoma line (A431) exposed or not to irradiation. Values of 79.84; 40.46; 22.37; 9.90 μM, represent, respectively, the IC50 of the AM solution and nanoparticle without and with light irradiation in an incubation time of 2 hours. Confocal microscopy analysis showed high cellular uptake of the nanoparticle. The results obtained demonstrate success in obtaining nanoparticles, promoting a significant improvement in the penetration of AM, capable of penetrating cells and causing a phototoxic effect. Furthermore, the research is unprecedented, as as far as we know, this is the first report of encapsulation of AM in PCL nanoparticles for application in skin cancer using PDT.